Big Data in operational decision making in the automotive industry in Asia period 2018 - 2023: literature review - Saavedra Mucha, Camila Antuane; Sanchez Torres, Jorge David; Sandoval Pezo, Ariane Ledda; Santiago Tito, Maria Alejandra; Vargas Ochoa, Ariana Grace; Cerna Huarachi, Delia Mercedes (LACCEI, 2025)
Abstract - The present article examines the influence of BigData on operational decision-making in the Asian automotiveindustry from 2018 to 2023. In a context where digitalization hastransformed business management, Big Data has becomeessential for real-time data processing, enhancing operationalefficiency and responsiveness to market demands. This qualitativestudy, using the PRISMA methodology, focuses on analyzing theimpact of technologies like batch processing, streamingprocessing, and NoSQL databases in decision-making acrosscountries such as China, South Korea, and India. Through acomprehensive literature review, it highlights how thesetechnologies have strengthened the industry's competitiveness inthe region.Keywords- Big Data, decision-making, automotive industry,batch processing, technologies.